Myricetin and chlorogenic acid from globe artichoke (Cynara cardunculus var. scolymus) as negative modulators of human Interferon I-α - Rosana Rotondo; Milagros Bürgi; Marianela Masin; Ana Adalid-Martínez; Jaime Prohens; Gustavo R. Rodríguez; Andrea M. Escalante (Heliyon)
The major phenolics of Cynara cardunculus var. scolymus were determined in extracts from leaves and edible parts of four genotypes named Gauchito, Madrigal, Gurí and Opal. The extracts were evaluated for their antioxidant capacity and the potential to inhibit the human recombinant alpha interferon (rhIFN-α). The extracts of edible parts of Madrigal, Opal and Gurí genotypes exhibited the highest antioxidant capacity in the autographic assay, while the highest levels of chlorogenic and di-caffeoylquinic acids were in Gurí extracts. Among the flavonoids -apigenin, luteolin, myricetin and quercetin-, the Gurí and Opal genotypes showed the highest myricetin content. Leaf extracts of Gurí and Madrigal reduced the expression of fluorescent protein representing the inhibition of rhIFN-α activity by 78 % and 65 %, respectively. The inhibition is greater when the extracts have as minimum content of chlorogenic acid (600 mg kg−1) and myricetin (6 mg kg−1) in the edible part. These results indicate that these artichoke genotypes may be of great interest as functional foods for their antioxidant activity and for inhibiting IFN-α, with possible new applications in preventing oxidative processes and alleviating diseases resulting from high levels of IFN-α.